Let $n > 1$ be an integer. Find, with proof, all sequences $x_1 , x_2 , \ldots , x_{n-1}$ of positive integers with the following three properties: (a). $x_1 < x_2 < \cdots < x_{n-1}$ ; (b). $x_i + x_{n-i} = 2n$ for all $i = 1, 2, \ldots , n - 1$; (c). given any two indices $i$ and $j$ (not necessarily distinct) for which $x_i + x_j < 2n$, there is an index $k$ such that $x_i + x_j = x_k$.
Problem
Source: USAJMO 2010, Problem 2
Tags: pigeonhole principle, arithmetic sequence, USAJMO, induction
29.04.2010 22:26
This is probably the least elegant way, but it's much better than nothing!
29.04.2010 22:54
You can also start from the end: a(1)+a(n-2)=a(n-1), etc. So a is 2,4,6,...,(2n-2).
29.04.2010 23:08
Don't forget the second part of the solution- You have to show that all sequences 2,4,6,...2(n-1) meet all of the criteria, not just that any sequence that meets it must be of this form
29.04.2010 23:37
I had a different proof (I hope it works). Here is an outline. Let $S=({x_1, x_2, \dots, x_{n-1}})$ 1) Prove that for all $j>i$, $(x_j - x_i) \in S$. 2) Now consider the sum $2n>x_{n-1} = (x_{n-1} - x_{n-1}) + (x_{n-2} - x_{n-3}) + \dots + (x_2 - x_1) + x_1$. 3) Pigeonhole on the above shows that for some $m$ either $x_m - x_{m-1}$ or $x_1$ is $1$ or $2$. 4) By (1) this is in $S$. 5) Induct on the case that it was $1$ and induct that it was $2$. 6) This shows either $S=({1,2,3, \dots 2n-1})$ or $S=({2,4,6, \dots, 2n-2})$. 7) In the first case, $|S| = 2n-1 > n-1$ which is a contradiction. Hence the only solution is $S={2,4,6, \dots, 2n-2}$.
30.04.2010 01:26
Goldey wrote: Don't forget the second part of the solution- You have to show that all sequences 2,4,6,...2(n-1) meet all of the criteria, not just that any sequence that meets it must be of this form Right. Should be fixed now.
30.04.2010 04:49
So we actually didn't need the fact the sequence was positive integers? My proof was really similar to quadraticfanatic's:
30.04.2010 05:14
I hope I get a point for just doing the if part...
21.04.2013 18:09
Would it be possible to see that $a_1$ must equal $2$ and then show that it constitutes the rest?
21.04.2013 18:14
Assuming you mean $x_1$, what do you mean "constitutes the rest"? And you might want to explain how you want to get that $x_1=2$, since this does not seem trivial.
21.04.2013 18:18
Caught my mistake. Thank you
11.01.2014 08:33
SnowEverywhere wrote: I had a different proof (I hope it works). Here is an outline. Let $S=({x_1, x_2, \dots, x_{n-1}})$ 1) Prove that for all $j>i$, $(x_j - x_i) \in S$. 2) Now consider the sum $2n>x_{n-1} = (x_{n-1} - x_{n-1}) + (x_{n-2} - x_{n-3}) + \dots + (x_2 - x_1) + x_1$. 3) Pigeonhole on the above shows that for some $m$ either $x_m - x_{m-1}$ or $x_1$ is $1$ or $2$. 4) By (1) this is in $S$. 5) Induct on the case that it was $1$ and induct that it was $2$. 6) This shows either $S=({1,2,3, \dots 2n-1})$ or $S=({2,4,6, \dots, 2n-2})$. 7) In the first case, $|S| = 2n-1 > n-1$ which is a contradiction. Hence the only solution is $S={2,4,6, \dots, 2n-2}$. this is exactly my solution,.good soln @snoweverywhere
11.01.2014 22:49
Better organized proof: Consider the sequence: $x_1 + x_1 < x_1 + x_2 <... <x_1 + x_{n-2}<x_1 + x_{n-1}=2n$. They are different terms of the original sequence except the last term. Because all the terms are greater than $x_1$, we should have $x_1 + x_1 =x_2$ and $x_1 + x_i =x_{i+1}$ for $1\leq i \leq n-2$. This implies that the original sequence is an arithmetic sequence with initial term $x_1$ and common difference $x_1$. $x_1+x_{n-1} =2n$ will imply $x_1=2$.
09.07.2015 23:00
We know $x_1+x_{n-1}=2n$. Because $x_{n-2}<x_{n-1}$, we have that $x_1+x_{n-2}=x_{n-1}$ because of property (c). Using similar logic we can conclude that $x_1+x_{n-3}=x_{n-2}$. We can continue this on until we have $x_1+x_2=x_3$. We subtract the first 2 equations we got to get that $x_{n-2}-x_{n-3}=x_{n-1}-x_{n-2}$. We can do this for all the equations we have to conclude that the sequence $x_1, x_2,..., x_{n-1}$ is an arithmetic sequence. But this does not guarantee that $x_1$ is a part of the arithmetic sequence, so we use the fact that $x_{n-1}+x_1=x_{n-2}+x_2$. This means that $x_2-x_1=x_{n-1}-x_{n-2}$ which does mean that $x_1$ is a part of the arithmetic sequence. Let the common difference of this arithmetic sequence be $d$. We use the equation $x_1+x_{n-2}=x_{n-1}$ to get the fact that $x_1=d$. This means our sequence is of the form $x_1, 2x_1, 3x_1,..., (n-1)x_1$. Now we use the equation $x_1+x_{n-1}=2n$ which gives $x_1=2$. So the only sequence that works is $2,4,6....2n-2$.
09.07.2015 23:10
How do you know that x_1+x_n-2=x_n-1? Why can't it be x_n-3?
09.07.2015 23:12
electrobrain wrote: How do you know that x_1+x_n-2=x_n-1? Why can't it be x_n-3? They are positive integers, and we are given that $x_{n-1}$ is greater than $x_{n-2}$ while $x_{n-3}$ is less than $x_{n-2}$. Rest should be self explanatory.
09.07.2015 23:15
I was asking why can the x_n-2 not be x_n-3 but I got it now. Thank you for replynig.
28.03.2016 00:09
Is this good?
13.12.2016 06:55
02.08.2017 06:34
Let $x_1=k$. Furthermore, let $X=(x_1, x_2,\dots x_n-1)$. It follows that $x_{n-1}=2n-k$. Now for all $m$, $1\leq m<n-1$, we have, by $(c)$ that $x_m+k\in X$. We must have that $x_{n-2}+k=x_{n-1}$. In a similar fashion, we can show that $x_{n-t}=n-tk$. Hence, $X=(k,2k,\dots (n-1)k)$. Since $k+(n-1)k=nk=2n$, we must have that $k=2$. Checking the conditions: (a) Yes, since $x_i<x_i+2$ (b) Yes since $2t+2(n-t)=2t$ (c) Yes, because $X$ is an arithmetic sequence Hence, $X=(2,4,8\dots 2n-2)$. $\square$
12.03.2023 21:23
Just note that \[x_1+x_{n-2}=x_{n-1}\]\[x_1+x_{n-3}=x_{n-2}\]\[\vdots\]\[x_1+x_2=x_3\]\[x_1+x_1=x_2\]so the numbers form an arithmetic sequence $\{2,4,\dots,2n-2\}$. $\blacksquare$
28.04.2023 16:34
v_Enhance wrote: So we actually didn't need the fact the sequence was positive integers? My proof was really similar to quadraticfanatic's:
Wow '0'
29.04.2023 18:58
hmmmm... I just looked at tons of arthimetic sequences and found that 2,4,6,8,10,12,14,16.....2n-2 works
21.07.2023 22:25
Solved with huashiliao2020.
29.07.2023 00:38
A very nice inductive question. The whole question is centred around $a_{n-i}-a_{n-1-i}=a_1$. This can be proven inductively by using pigeonhole principle and strictly increasing condition on the last condition. Then we have $a_i=ki$ for some k and solving get $k=2$. The other direction is much easier. Full proof here https://infinityintegral.substack.com/p/usajmo-2010-contest-review
15.08.2023 12:13
I claim that the only sequence is $x_i=2i$. It is easy to see that such a sequence suffices the condition. Now we prove that this is the only one. Firstly, for some $n$, we prove that $x_i=i\cdot x_1$. We proceed using induction. The base case $x_1=1\cdot x_1=x_1$ is clearly true. Now assume the induction hypothesis for some $k-1<n-1$, and we prove it for $k$. Consider the following sequence.\[x_1+x_{n-k},x_2+x_{n-k},\ldots,x_{k-1}+x_{n-k}.\]Note that this sequence has $k-1$ terms in it. Firstly, we have that $x_k+x_{n-k}=2n$ and the fact that $x_i<x_k$ for all $1\le i\le k-1$. So this gives us that $x_i+x_{n-k}<x_k+x_{n-k}=2n$ which means that we will get some $x_j$ for each $i$ such that $x_j=x_i+x_{n-k}$. Now clearly from the increasing condition of the sequence, we get that $j\ge n-k+1$. So each $x_j$ belongs to the following sequence.\[x_{n-(k-1)},x_{n-(k)},\ldots,x_{n-1}.\]So note that this sequence also has $k-1$ terms. So this forces that the equality occurs in each of the values of $x_j$ from both the sequences. So this gives that $x_1+x_{n-k}=x_{n-(k-1)}$, which further gives that $x_1+(2n - x_{n-(n-k)})=2n - x_{n-((n-k+1)}\implies x_1 - x_k = -x_{k-1}\implies x_1+x_{k-1}=x_k$. Now using our induction hypothesis, we get that $x_{k-1}=(k-1)x_1$ which finally gives $x_k=k\cdot x_1$. Now then, we finally get that $x_{n-1}=(n-1)x_1$. Putting this into $x_1+x_{n-1}=2n$, we get that $x_1=2$ and we are done.
06.12.2023 07:40
We claim the only possible sequence is if $x_i=2i$. This sequence clearly works, and we now prove it is the only one.// First of all, consider $x_1+x_{n-2}$. As $x_1>0$, it has to be more than $x_{n-2}$, which implies that it must be $x_{n-1}$. As each of the following sums are in decreasing order, from top to bottom: \[x_1+x_{n-2}\]\[x_1+x_{n-3}\]\[\dots\]\[x_1+x_1,\]and there are $n-2$ of them, we can say that: \[x_1+x_{n-2}=x_{n-1}\]\[x_1+x_{n-3}=x_{n-2}\]\[\dots\]\[x_1+x_1=x_2.\] Therefore, it is easy to see that $x_{i}=ix_1$. Therefore, $nx_1=2n$, or $x_1=2$, as desired.
06.12.2023 08:37
Note that we are given, $x_1 < x_2 < \dots < x_{n-1}$ $x_1 + x_{n-1} = x_2 + x_{n-2} = x_3 + x_{n-3} = \dots = 2n$ From the final condition we find $x_1 + x_2$, $x_1 + x_3$, $\dots$, $x_1+x_{n-2}$ all belong to $(x_i)$. Clearly $x_1 + x_{n-2} = x_{n-1}$ or that $$x_{n-2} = x_{n-1} - x_1$$Then $x_1 + x_{n-3} = x_{n-2}$, which in turn gives, $$x_{n-3} = x_{n-1} - 2x_1$$and so on. Inducting downwards we find $$x_{n-1-k} = x_{n-1} - kx_1$$However then $x_1 = x_{n-1} - (n-2)x_1$ which gives $nx_1 = 2n$, or $x_1 = 2$. Now from our induction we find the sequence of $(x_i)$ are simply the even integers from $2$ to $2n - 2$.
22.12.2023 23:50
Consider the sequence $x_1+x_1, x_1+x_2, \dots, x_1+x_{n-1} = 2n$. Each of the $n-2$ terms before $2n$ are obviously less than $2n$, and they must be part of the sequence $x_1, x_2, \dots, x_{n-1}$. This means we must necessarily have \begin{align*} x_1+x_1 &= x_2, \\ x_1+x_2 &= x_3, \\ \dots &\phantom{=} \\ x_1+x_{n-2} &= x_{n-1}. \end{align*} Hence, $x_k = kx_1$, and plugging this in gives \[x_1+(n-1)x_1=2n \implies x_1=2.\] Thus, $x_n = \boxed{2n}$, which is easily checked to be true.
06.01.2024 14:57
We find that \[x_1 < x_1 + x_1 < x_1 + x_2 \dots x_1 + x_{n-2}\]are all in $x_i$, due to $(c)$, and since there are $n-1$ terms, this sequence must be equivalent to \[x_1, x_2, \dots, x_{n-1}\]So, we can rewrite each term as $ix_1$. $\newline$ \[x_1 + x_{n-1} = 2n\]can be rewritten as \[x_1 + (n-1)x_1 = 2n \implies nx_1 = 2n \implies x_1 = 2\]Due to the fact that each term is equal to $ix_1$, this sequence is just $x_i = 2i$.
19.01.2024 06:25
Due to the third condition, we know the sequence $x_2, x_3, \ldots, x_{n-1}, 2n$ must correspond with the terms of \[x_1+x_1 < x_1+x_2 < \ldots < x_1+x_{n-2} < x_1+x_{n-1} = 2n.\] Thus we know $x_k = k \cdot x_1$ for $1 \leq k \leq n-1$, from which the second condition tells us our only solution is $\boxed{x_i = 2i}$. $\blacksquare$
24.02.2024 06:32
I goofed last time; I claim that the only possible sequence is $2$, $4$, $6$, $\dots$, $2n-2$. Note that by problem conditions, we have that \[x_1+x_{n-1}=2n,\]but we also have that \[x_1+x_{n-2}=x_j,\]for some integer $j$. However, since $x_1<x_2<\dots<x_{n-1}$, we must have that $x_{n-2}=x_{n-1}-x_1$. Similarly, we get that \[x_k=x_1+x_{n-3}<x_1+x_{n-2}=x_{n-1},\]meaning that $k=n-2$. Continuing this, we get that our sequence must be $x_1$, $2x_1$, $\dots$, $(n-1)x_1$, and since $x_1+x_{n-1}=2n$, we also get that $x_1$ must be equal to $2$. Therefore the only possible sequence is $2$, $4$, $6$, $\dots$, $2n-2$, which indeed works, finishing the problem.
09.03.2024 21:40
is this correct? why is my solution different from everyone else lol For any two terms $x_i < x_j$, notice that the following terms are also in the sequence \[x_i, x_j \rightarrow 2n-x_j \rightarrow 2n-x_j+x_i \rightarrow x_j-x_i\]This is essentially a stronger version of the converse of condition 3. From here, note that we may prove that each element is a multiple of $x_1$ by induction. The only possible sequences are now $1,2,\dots, n-1$ and $2,4,\dots,2(n-1)$. The first sequence doesn't work, while the second one does.
26.09.2024 16:11
My solution is different from others so did I fakesolve? We separate the problem into $2$ cases which both are analogous. Case 1. $n-\text{is even}$
Case 2. $n-\text{is odd}$
Since in both cases we have: $\{x_1,x_{k_1}, \dots , x_{k_{n-2}} \}=\{x_1,x_2, \dots, x_{n-1} \}$ we get: $x_1=x_1 , x_2=x_{k_1} , x_3=x_{k-2} , \dots , x_{n-1}=x_{k_{n-2}}$ So $x_1+x_1=x_{k_1}=x_2 \implies x_1+x_1=x_2 \implies x_2=2 \cdot x_1$ $x_1+x_2=x_{k_2}=x_3 \implies x_1+x_2=x_3 \implies x_3=x_1+x_2=x_1 + 2 \cdot x_1=3 \cdot x_1 \implies x_3=3 \cdot x_1$ $x_2+x_2=x_{k_3}=x_4 \implies x_2+x_2=x_4 \implies x_4=2 \cdot x_2=2 \cdot 2 \cdot x_1= 4 \cdot x_1 \implies x_4=4 \cdot x_1$ $x_2+x_3=x_{k_4}=x_5 \implies x_2+x_3=x_5 \implies x_5=x_2+x_3=2 \cdot x_1 + 3 \cdot x_1 =5 \cdot x_1 \implies x_5= 5 \cdot x_1$ $x_3+x_3=x_{k_5}=x_6 \implies x_3+x_3=x_6\implies x_6=x_3+x_3=3 \cdot x_1 + 3 \cdot x_1=6 \cdot x_1 \implies x_6=6 \cdot x_1$ $\dots$ $x_{\frac{n}{2}-1}+x_{\frac{n}{2}-1}=x_{k_{n-3}}=x_{n-2} \implies x_{\frac{n}{2}-1}+x_{\frac{n}{2}-1}=x_{n-2} \implies x_{n-2}= x_{\frac{n}{2}-1}+x_{\frac{n}{2}-1}=2 \cdot x_{\frac{n}{2}-1} = 2 \cdot (\frac{n}{2}-1) \cdot x_1=(n-2) \cdot x_1 \implies x_{n-2}=(n-2) \cdot x_1$ Now again by $(b) \implies$ $x_2+x_{n-2}=2n \implies 2 \cdot x_1 + (n-2) \cdot x_1 =2n \implies n \cdot x_1=2n \implies x_1=2 So x_1=2, x_2=2 \cdot x_1=2 \cdot 2=4 , x_3=3 \cdot x_1= 3 \cdot 2=6 , \dots x_{n-1}=(n-1) \cdot x_1=(n-1) \cdot 2=2n-2$ Hence $(x_1,x_2, \dots , x_{n-1}=(2,4, \dots ,2n-2)$
21.01.2025 07:34
Observe that property (b) is equivalent to $$i+j < n \iff x_i+x_j < 2n.$$Therefore, $$x_1 < x_1+x_1 < x_1+x_2 < \cdots < x_1+x_{n-2} < 2n.$$However, each of these sums are some $x_k$ but since $$x_2<x_3<\cdots < x_{n-1} < 2n$$it follows that $x_1+x_k=x_{k+1}$ for each $k=1, 2, \dots, n-2.$ Thus $x_2=2x_1, x_3=3x_1,$ etc. This yields $2n=x_1+x_{n-1}=x_1+(n-1)x_1 \implies x_1=2,$ and it follows that the sequence is $$2, 4, 6, \cdots, 2n-2.$$It is easy to show that this works.